WebGIS Based Poverty Level Analysis (Case Study Of Wonosari Sub-District Boalemo Regency) - Irwan Muis; Sunarty Suly Eraku; Syahrizal Koem (Universitas Negeri Gorontalo, 2019)
Information on household poverty level in Wonosari Sub-district area is still very difficult to access by all parties. Therefore, this study aims to analyze poverty level and map of the spatial distribution of webGIS-based poor households in the site area. In determining the number of samples, descriptive statistical analysis techniques focused on assessing and describing the poverty level of each household. GIS analysis used GIS Application 2.18 to map the spatial distribution of poor households and regional poverty levels. GIS Application has been equipped with 2 web tools that are able to display webGIS-based maps. The results shows that the poverty level of households is in the poor category with a percentage of 72% of households, 14% of households are in the extremely poor category and 14% are in the fairly poor category. and 1 village is in a fairly poor category. This is a village that was built with a view that can be accessed by various PCs, laptops and android media so that the maps information from an analysis of household poverty levels and the spatial distribution of poor households can be accessed on the webGIS that has been built.